Improving composting process by controlling aeration time - Abd Hamid, Khairul Bariyah; Abu Samah, Mohd Armi; Mohd Zainudin, Mohd Huzairi; Yunus, Kamaruzzaman (Research India Publications, 2016)
Composting is a biological treatment process to treat organic waste. There are many parameters that affecting it process. Temperature, pH, aeration, moisture content and microorganism are a few factors controlling composting process. Missing one of the parameter will result in incomplete process. Thus, the objective of this study is to improving composting process by controlling one parameter of composting which is aeration. Before starting the composting process, the food wastes are spread on a canvas to drain out excess water. After that, the food wastes are grinded and let out to rest about 1 day under sunlight. 12 kg of grinded and dried food waste was thrown into composting bin and the first data was recorded. The food waste in the composting bin has been rotated for 15 minutes and let to rest another 15 minutes. The data collection has been done for the total 53 hours in 3 days. Range for compost temperature, compost pH, surrounding temperature and surrounding relative humidity during the process are 26°C - 45°C, 4.24 – 5.81, 26.4°C – 35.2°C, and 54% - 81%, respectively. Results show that with the constant aeration time, time taken for composting process to complete become shorter. Further research can be done to compare various aeration times for composting. Thus, we can come out with the standard of aeration of composting process. This will enhance the composting process technique that help to solve the problem of increasing food waste and prolong the landfill lifetime.